Meeting The Needs of The Muslim Communication Community During The Pandemic - Bibi Jan Mohd Ayyub (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2022)
This paper serves as an analysis and a review based on an exploratory two sharing session amongst Muslim teachers in Singapore. This paper seeks to dismantle the multifaceted effects of the Covid-19 pandemic, thereby allowing room to explore and analyse how different layers of the Singaporean population grapple with these unprecedented challenges, specifically within the Muslim population. This paper will also review and explore various government policies and measures that were taken to ring fence these issues, thereby adding to the current literature that are in tandem to assist countries with better preparedness in future. In conclusion, this paper aims to provide some valuable insights on how individual especially Muslim teachers can choose to positively respond and adopt self-care to nurture their holistic well-being in a cosmopolitan city of Singapore.